Taste Receptor Cells in Mice Express Receptors for the Hormone Adiponectin. (24th May 2019) - Crosson, Sean M; Marques, Andrew; Dib, Peter; Dotson, Cedrick D; Munger, Steven D; Zolotukhin, Sergei
Abstract: The metabolic hormone adiponectin is secreted into the circulation by adipocytes and mediates key biological functions, including insulin sensitivity, adipocyte development, and fatty acid oxidation. Adiponectin is also abundant in saliva, where its functions are poorly understood. Here we report that murine taste receptor cells (TRCs) express specific adiponectin receptors and may be a target for salivary adiponectin. This is supported by the presence of all three known adiponectin receptors in transcriptomic data obtained by RNA-seq analysis of purified circumvallate (CV) taste buds. As well, immunohistochemical analysis of murine CV papillae showed that two adiponectin receptors, ADIPOR1 and T-cadherin, are localized to subsets of TRCs. Immunofluorescence for T-cadherin was primarily co-localized with the Type 2 TRC marker phospholipase C β2, suggesting that adiponectin signaling could impact sweet, bitter, or umami taste signaling. However, adiponectin null mice showed no differences in behavioral lick responsiveness compared with wild-type controls in brief-access lick testing. AAV-mediated overexpression of adiponectin in the salivary glands of adiponectin null mice did result in a small but significant increase in behavioral lick responsiveness to the fat emulsion Intralipid. Together, these results suggest that salivary adiponectin can affect TRC function, although its impact on taste responsiveness and peripheral taste coding remains unclear.